2019
DOI: 10.1002/pssb.201800589
|View full text |Cite
|
Sign up to set email alerts
|

III‐Nitride Nanowires as Building Blocks for Advanced Light Emitting Diodes

Abstract: This article presents a discussion on the role of nanowire (NW) structures, prepared by reactive ion etching (RIE), in planar III‐nitride light emitting diodes (LEDs) for increasing the functionality, improving the crystalline quality, enhancing the quantum efficiency of radiative recombination, and improving the light extraction efficiency. The methods of NW fabrication by RIE, of suppressing the adverse effects of RIE‐related damage, and of incorporating air voids into the NWs are also discussed. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 75 publications
(151 reference statements)
0
11
0
Order By: Relevance
“…The nanowire (NW) configuration in semiconductor systems such as oxides, nitrides, and arsenides is highly promising for the next generation nanoscale photonic, optoelectronic and photovoltaic devices thanks to the characteristic large area to volume ratio [1][2][3]. In particular, for light-emitting devices, it was demonstrated that group III-nitride (III-N) NWs can achieve higher light extraction compared to their 2D counterparts [4,5]. Furthermore, the efficient strain relaxation during NW growth allows the use of highly lattice-mismatched substrates (e.g., silicon) with a reduced density of extended defects compared to thin-film epitaxy, facilitating their compatibility with current microtechnology.…”
Section: Introductionmentioning
confidence: 99%
“…The nanowire (NW) configuration in semiconductor systems such as oxides, nitrides, and arsenides is highly promising for the next generation nanoscale photonic, optoelectronic and photovoltaic devices thanks to the characteristic large area to volume ratio [1][2][3]. In particular, for light-emitting devices, it was demonstrated that group III-nitride (III-N) NWs can achieve higher light extraction compared to their 2D counterparts [4,5]. Furthermore, the efficient strain relaxation during NW growth allows the use of highly lattice-mismatched substrates (e.g., silicon) with a reduced density of extended defects compared to thin-film epitaxy, facilitating their compatibility with current microtechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, nanowires made of direct-band gap III–V nitride semiconductors (e.g., gallium nitride (GaN)) have attracted a great deal of attention, since these 3D GaN building blocks have several superior properties compared to other semiconductor materials, such as wide band gap, relatively high electron mobility, thermal stability, and robustness. This leads to their usages not only in solid-state lighting as indium gallium nitride (InGaN)/GaN light-emitting diodes (LEDs) but also in other applications (e.g., monolithic integrated nanofield-effect transistors (FETs), , nanomechanical force sensors, , and noninvasive biomedical sensors). In the later applications, InGaN/GaN LED with blue light emission (λ = 465 nm) can even enhance the biosensing platform with monolithic optical excitation and simultaneous biomolecule imaging for lab-on-chip microscopy. , …”
Section: Introductionmentioning
confidence: 99%
“…Even so, the problems on distribution, morphology, and size uniformity for the grown nanowires may limit a reliable nanoscale device fabrication that often needs precisely controlled nanostructures. Moreover, so far, a large scale fabrication method with homogeneous nanowires still cannot be resolved by bottom-up methods. , Therefore, a top-down approach combining nanolithography and etching processes is explored as an alternative method to obtain a higher control in reproducibility and addressability of the produced nanowires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A.Ya. Polyakov et al discuss the role of nanowire structures prepared by reactive ion etching in planar III‐nitride light emitting diodes in increasing functionality, improving the crystalline quality, enhancing the quantum efficiency of radiative recombination and the light extraction efficiency. S. Lancaster et al revealed the influence of boron antisite defects on the electrical properties of MBE‐grown GaAs nanowires.…”
mentioning
confidence: 99%